The Influence of Competitive Advantage Strategy Implementation and Total Quality Management (TQM) on Company Performance with Management Accounting Information Quality as a Moderating Variable (Empirical Study on State-Owned Enterprises in Ambon City) - Pattinasarany, Pattinasarany; Frans, Leddy; Basuki, Ferry. H.; Hariyanti, Dwi (SEAN Institute, 2024)
This study aims to examine the effect of the Application of Competitive Advantage Strategy and Total Quality Management on Company Performance with the Quality of Management Accounting Information as a moderating variable. This research uses a quantitative approach. The population in this study were State-Owned Enterprise Companies in Ambon City. The sample in this study were division / business unit managers and general managers, each of which was represented by 2 BUMNs. The results showed (1) Implementation of Competitive Advantage Strategy has a positive effect on company performance, (2) Total Quality Management has a positive effect on company performance, (3) Quality of Management Accounting Information cannot moderate the relationship of Implementation of Competitive Advantage Strategy on company performance, (4) Quality of Management Accounting Information cannot moderate the relationship of Total Quality Management on company performance.